PENGEMBANGAN DAYA CIPTA ANAK MELALUI AREA BALOK PADA ANAK KELOMPOK B DI TK PGRI PEMBINA KOTA BIMA TAHUN AJARAN 2022/2023 - edajubaedah1234 eda Jubaedah; Hurin Innihayatus Sa'adah; Saddam S.Pd., M.Pd (Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2023)
The purpose of this study is to develop children's inventiveness in improving children's abilities in congestive aspects following predictable patterns. That is, the level of congestive development of children is in line with the level of development of children's mental age so that in developing children's inventiveness it is necessary to pay attention to the following: Adequate facilities, stimulating environment, encouragement and sufficient time The block area is a very important block game for a child's cognitive development in various areas including language, social skills, knowledge, mathematics, motor and moderate internal abilities learn. Block area tools are blocks of various sizes, puzzles, cubes, cardboard files, traffic signs and so on. The results of the study obtained an illustration that teachers are very engaged in developing children's inventiveness through the beam area in the students of the Bima City Supervisory PGRI Kindergarten for the 2022/2023 academic year. This research method uses qualitative descriptive research because it aims to explain the development of children's inventiveness through the beam area in group B at TK PGRI Pembina Kota Bima. Thus, learning activities in developing children's inventiveness through the beam area in Group B students at the Bima City Supervisory PGRI Kindergarten in 2022/2023 can be concluded to be successful. Keywords : Beam Area Inventiveness